Optimasi Penempatan Distributed generation dan Kapasitor Bank Berbasis Particle Swarm Optimization untuk Meningkatkan Kinerja Sistem Distribusi Kota Sabang - Muhajir Muhajir; Suriadi Suriadi; Melinda Melinda (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2026)
The Sabang electricity system is an isolated grid system that relies on diesel power plants with long distribution lines, which can cause high losses and voltage drops. This study aims to find the optimal placement of Distributed Generation (DG) and capacitors using Particle Swarm Optimization (PSO) Method to reduce losses and voltage deviation, with a voltage limit of 5% on a 20 kV system. Simulation results show that without DG and capacitors, losses reach 26 kW at peak load and 24.4 kW at normal load, with low voltages at some buses. After optimization, the combined use of DG and capacitors reduces losses by 50.82% at normal load and 51.15% at peak load. The voltage profile also improves by about 200 - 350 V at each bus, bringing it closer to the nominal value of 20 kV. Compared with Genetic Algorithm (GA), PSO provides better results, with 0.45 - 3.79% lower active power losses and 0 - 7.40% lower reactive power losses. This proves that PSO is effective in improving the efficiency, voltage quality, and reliability of isolated distribution systems.Keywords – Distributed generation (DG), Losses, Particle Swarm Optimization (PSO), Renewable Energy